Design a reconfigurable U-slot rectangular microstrip patch antenna for a multiband applications / Mohamad Asri Shafie - Shafie, Mohamad Asri (2014)
In this paper, a reconfigurable U-slot rectangular microstrip patch antenna for multiband applications is proposed. This prototype antenna is designed for mobile and wireless applications. Two pin diodes were placed and used as a switch at two specific positions of the slot. The proposed designed was simulated using the Computer Simulation Technology (CST) Software. Both simulation and measurement results were compared and analyzed to identify the actual characteristics of this prototype antenna.